Overcoming Post-Operative Anabolic Resistance: The Integrated Role of Protein Nutrition and Physical Rehabilitation in Orthopedic Patients - Kubala, Karolina; Tesyna, Julia; Obszańska , Aleksandra; Tomczyszyn, Jakub; Czapla, Melania; Marchlik, Kamil (Quality in Sport, 2026)
Introduction: Orthopedic surgery and subsequent disuse trigger a severe systemic stress response. This hostile environment induces anabolic resistance. Consequently, skeletal muscle loses its sensitivity to nutritional inputs and mechanical loading. At the molecular level, the process is driven by a failure of the mTORC1 signaling pathway and accelerated FOXO-mediated proteolysis. Ultimately, these mechanisms cause rapid muscle atrophy, a negative nitrogen balance, and functional decline. Aim: The aim of this narrative review is to examine the molecular and physiological mechanisms of post-operative anabolic resistance and to evaluate how perioperative protein nutrition and mechanical loading combine to restore functional capacity in orthopedic patients. Material and methods: This study was conducted as a narrative review of literature addressing the pathophysiology of post-operative anabolic resistance and integrated recovery strategies in orthopedic patients. A comprehensive literature search was performed using the electronic databases PubMed/MEDLINE, Scopus, Web of Science, the Cochrane Library, and Google Scholar. Results: Post-operative anabolic resistance represents a failure of the mTORC1 signaling path, elevating the leucine threshold needed for net muscle balance. Mechanical loading during rehabilitation acutely enhances muscle sensitivity to amino acids. Consequently, clinical outcomes are optimized when elevated, leucine-rich protein doses (30–40 g/meal, totaling 1.2–2.0 g/kg/day) are evenly distributed. Compared to integrated interventions, standalone nutritional or mechanical protocols exhibit significant variability in their functional endpoints. Conclusions: Post-operative muscle loss is a multi-factorial process requiring a multidisciplinary approach. Overcoming anabolic resistance and accelerating recovery requires fully integrating nutrition into orthopedic rehabilitation, rather than treating it as an isolated intervention.